Sharing and Knowing Learning Model: Is it Effective in Increasing Student Learning Activities and Understanding? - Aang Rohyana; Dicky Tri Juniar; Jusuf Blegur (Universitas Pendidikan Ganesha, 2023)
Learning design should ideally support increased learning activities and student understanding, but in fact there are still various problems in its implementation, for example students lack concentration, are less active in asking questions, and are low motivated in seeking information. This study aims to analyze the improvement of the Sharing and Knowing (SHARK) learning model on student learning activities and understanding of the material